Cardiovascular involvement during the acute phase of Carrion’s disease or human Bartonellosis: A 20-year experience in Cayetano Heredia National Hospital - Maguiña Vargas, Ciro (2008)
Introduction: Carrions disease is considered a re-emerging disease in Peru, and it leads to several non-infectious and infectious complications.Objectives: To assess cardiovascular complications (CC) during the acute phase of this disease.Methods: An observational study was conducted at Cayetano Heredia Hospital (HNCH) from 1987 to 2007. Adult patients with a confirmed diagnosis of Bartonellosis were included.  Results: 68 patients were included (52 males, mean age 25,7 years). No one had prior cardiovascular disease. Main clinical findings were: fever (99%), hepatomegaly (79%), jaundice (74%), tachycardia (74%), tachypnea (71%), systolic murmur (68%), dyspnea (62%), hepatojugular reflux (19%) and jugular ingurgitation (15%). Sixty-four chest X-ray films showed the following findings: 44% cardiomegaly, 20% pulmonary congestion, and 16% pleural effusion. Transthoracic echocardiogram was performed in 42 patients: 38% had pericardial effusion, 19% dilated left atrium, and 17% dilated left ventricle. Thirty-six patients developed CC: congestive heart failure was found in 92%, effusive pericarditis in 44%, acute pulmonary edema in 36%, cardiogenic shock in 17%, pericardiac tamponade in 11% and myocarditis in 11%. Patients who developed CC had a shorter time of illness before admission (p= 0.01), stayed longer in the hospital (p= 0.014), used more chloramphenicol (p= 0.009) and less ciprofloxacin (p= 0.004), they developed more infectious complications (p= 0.002), and they were more frequently admitted in the ICU (p= 0.004), compared to patients who did not develop CC.Conclusion: CC are frequent in Bartonellosis. A variety of cardiovascular syndromes was observed, and they were associated to a shorter time of illness before admission, longer hospitalizations, more use of chloramphenicol and less use of ciprofloxacin, more frequent infectious complications, and more admissions to ICU, but they did not have higher mortality.